Mutism and rigidity due to antipsychotic‐induced catatonia improved by hemodialysis: A case report - Rintaro Fujii; Ryota Suga; Norihito Satoh; Yasuo Watanabe; Reiji Yoshimura (PCN Reports)
Abstract Background Catatonia is a psychomotor syndrome linked to various medical conditions. Among these, several reports have described antipsychotic‐induced catatonia (AIC). Treatment typically includes benzodiazepines and electroconvulsive therapy. Here, we report a rare case of AIC that showed an improvement in symptoms under hemodialysis. Case Presentation A 79‐year‐old man with diabetic nephropathy was admitted with acute renal failure and metabolic acidosis. Hemodialysis was initiated, and his acute renal failure and metabolic acidosis were mild. On Day 11, following an intramuscular injection of haloperidol (2.5 mg) for agitation the previous day, he developed mutism, rigidity, and resistance to mouth‐opening, leading to a diagnosis of AIC. His symptoms improved dramatically during the course of hemodialysis, with no recurrence after seven sessions. He was discharged after 49 days and did not experience recurrence of catatonia in the following 12 months. Conclusion While this case showed a rapid improvement in AIC following hemodialysis, no robust evidence implicating AIC and hemodialysis has been reported to date. This case suggests the potential role of hemodialysis in improving AIC symptoms. Further research to better understand the relationship between AIC and hemodialysis and the underlying mechanisms of catatonia is required.